Membership Participation and Sustainability of Government-Driven Rural Development Projects in Abia State of Nigeria - Okala Agwu Uche; Ijeoma Blessing Uche; Nma Njoku Chukwu; Bonaventure Ngozi Nwokeoma (Transylvanian Review of Administrative Sciences, 2019)
Membership participation has become a veritable strategy for empowerment in the development scene. The participation of community members in development activities enhances capacity building. Sustainable development has to do with participatory development, human development and environmental protection. This study examines participation of community members and sustainability of government-driven rural development projects in Abia State of Nigeria. The purposive sampling technique was adopted in the study. The sample comprised of 6 communities from 6 Local Government Areas (LGAs) in the state. The focus group discussions (FGDs) and in-depth interviews (IDIs) were the instruments for data collection. The sample size used in the study was 72 FGD participants and 6 IDI respondents. Data generated for the study were analyzed in quotes. The study revealed that all the rural communities under study have benefitted from government projects. It also shows that the executed projects have impacted on the quality of lives of the people. Furthermore, the study revealed that membership participation in the execution of projects is low and this has implications in project sustainability.